Analysis of motion and fatigue life of Mimosa pudica - Tang, Zhi Min, Cheryl (2014)
Mimosa pudica, a sensitive plant, is known to fold their leaves when stimulated by touch only to reopen a few minutes later. This folding action travels along the leaflet to other parts of the plant causing the other leaflets to close as well. They are also observed to be controlled by a biological clock, closing their leaves at nightfall. Many different types of researches has been done on Mimosa pudica and this report would analyse the various studies done on them ranging from leaf movement, the causes of stimulation as well as some models that have already been developed based on the Mimosa pudica and its structure. Furthermore, other types of the studies done on Mimosa pudica will also be discussed and these include its allelopathic reactions, its effects on animals and its pharmaceutical applications. Lastly, the response of Mimosa pudica specimens with respect to mechanical stimulations will be analysed and discussed. The focus of the discussion would be on the fatigue life of Mimosa pudica as it is a new and independent study which has never been recorded and discussed in other research papers.